Electric Pain Control - Jenkner, F. L. (Springer Vienna, 1995)
After a very brief introduction to neurophysiology of pain and the influence of weather on pain the selection of an optimal current by the author is presented. This optimal current applied via specially unequal electrodes on distinct sites gives pain reduction of a surprisingly high degree. If the reader follows the advice using the (photodocumented) positions of electrodes the same degree of pain reduction will be reached to the benefit of the patient. Forms for organizing a pain clinic and ample literature citations facilitate the application of this new approach to therapy of pain